The Role of Securities-Based Crowdfunding in Advancing the Local Economy for Small and Medium-Sized Enterprises (SMEs) - Astuti, Nanin Koeswidi; Suhariningsih, Suhariningsih; Sukarmi, Sukarmi; Hamidah, Siti (IJBLE Scientific Publications Community Inc., 2024)
This article conducts an analysis of securities-based crowdfunding (SCF) as an alternative funding source outside traditional banking institutions. It explores whether the primary objective of SCF in Indonesia is indeed to advance the economy of the people, particularly focusing on Small and Medium Enterprises (SMEs). The article presents various perspectives on the concept of collective funding, where a group of contributors finance SME and startup projects, enabling these ventures to operate and progress. This approach aligns with the principles of a people-centered economy, which is characterized by an economy of the people, by the people, and for the people. The aim is to foster the people's economy, imbued with the characteristics of the Indonesian society which is religious and believes in sharing prosperity with others, as mandated by Article 33 of the 1945 Constitution of the Republic of Indonesia.